Geranylgeraniol increased mineralization in osteoblasts treated with low concentration of alendronate: A preliminary study - Patntirapong, Somying; Korjai, Nareerat; Matchimapiro, Monticha; Sungkaruk, Paphada; Suthamporn, Yauwaluk (Mahidol Dental Journal, 2020)
Objective: To investigate the effects of geranylgeraniol (GGOH) on alendronate (ALN)-treated osteoblast viability and bone nodule formation. Materials and methods: MC3T3, murine osteoblast precursors, were cultured with ALN (0 and 1 µM) and GGOH (0, 10, and 50 µM). The viability of MC3T3 was determined by MTT assay at 3 and 6 days. After 3 weeks, bone nodule formation was evaluated by alizarin red S assay. Results: Addition of ALN did not affect cell viability of MC3T3 at 3 and 6 day incubation. Bone nodule formation of ALN-treated osteoblasts exhibited lower red staining compared with that of untreated control. In the presence of ALN, there was no significant difference on viability between cells treated with GGOH and those without GGOH for 3 and 6 days. On the contrary, GGOH addition significantly increased the percentage of bone nodule formation in osteoblasts treated with ALN. Conclusion: Low concentration of ALN reduced bone nodule formation produced by osteoblasts. Exogenous GGOH could reverse the inhibitory effect of ALN. Thus, GGOH could be a potential therapy for the conditions caused by the reduction in bone formation such as bisphosphonate-related osteonecrosis of the jaw and atypical fracture of femoral diaphysis.